Socioeconomic status and survival among older adults with dementia and depression. (June 2014) - Chen, Ruoling; Hu, Zhi; Wei, Li; Wilson, Kenneth
Abstract : Background: People from lower socioeconomic groups have a higher risk of mortality. The impact of low socioeconomic status on survival among older adults with dementia and depression remains unclear. Aims: To investigate the association between socioeconomic status and mortality in people with dementia and late-life depression in China. Method: Using Geriatric Mental Status – Automated Geriatric Examination for Computer Assisted Taxonomy (GMS-AGECAT) we interviewed 2978 people aged ⩾60 years in Anhui, China. We characterised baseline socioeconomic status and risk factors and diagnosed 223 people with dementia and 128 with depression. All-cause mortality was followed up over 5.6 years. Results: Individuals with dementia living in rural areas had a three times greater risk of mortality (multivariate adjusted hazard ratio (HR) = 2.96, 95% CI 1.45–6.04) than those in urban areas, and for those with depression the HR was 4.15 (95% CI 1.59–10.83). There were similar mortality rates when comparing people with dementia with low v. high levels of education, occupation and income, but individuals with depression with low v. high levels had non-significant increases in mortality of 11%, 50% and 55% respectively. Conclusions: Older adults with dementia and depression living in rural China had a significantly higher risk of mortality than urban counterparts. Interventions should be implemented in rural areas to tackle survival inequality in dementia and depression.